Going Beyond Childhood and Gender-Based Violence: Epigenetic Modifications and Inheritance - Letizia Li Piani; Edgardo Somigliana; Laila Giorgia Micci; Gaia Spinelli; Giussy Barbara (Mary Ann Liebert, 2024)
Being exposed to childhood or gender-based violence is associated with subsequent adverse events in individual lives. Not only can it cause psychological distress but violence survivors suffer from a range of long-term adverse health outcomes, including higher morbidity, higher mortality, and higher risk of chronic diseases. Epigenetics may be involved in the determinisms of these long-term detrimental effects. A large body of evidence supports this biological mechanism to explain violence-related health impairment in the long term. However, studies specifically focusing on violence are scant and nonunivocal. Epigenetic modifications of genes involved in stress response and in the hypothalamus?pituitary?adrenal axis regulation are the most commonly and consistently reported. Promising evidence also emerged for the use of epigenetic clocks. Finally, although very limited, there is evidence supporting the notion that long-term health impairment may be transmitted from one generation to the other. Overall, despite promising, available evidence is yet incomplete. The overlap with pure psychological mechanisms of health impairment exposes the findings to confounders and hampers strong conclusions. Based on a literature search on PubMed/Embase, our narrative review aims to illustrate the evidence concerning the potential bond between epigenetics and violence, including also possible impacts on later generations. The goal is to encourage further research to help the development of a more holistic approach for such a vulnerable and often neglected population. Further research is warranted to precisely disentangle the role of epigenetics in mediating the long-term health impairment associated with childhood or gender-based violence. Advances in this area may open new avenues of treatment. Epigenetic modifications may indeed be reversible and could be an attractive therapeutic target to minimize the long-term consequences of childhood or gender-based violence.